2011
DOI: 10.1111/j.1756-2589.2011.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Latino Adolescent Substance Use in the United States: Using the Bioecodevelopmental Model as an Organizing Framework for Research and Practice

Abstract: Research has indentified numerous risk and protective factors related to adolescent alcohol and other drug (AOD) use. However, most theoretical models do not account for nuances attributable to variations in culture or how these may influence prevention and treatment models. In this article, we have 4 primary purposes: First, we present an extensive and critical review of the literature on adolescent AOD use among Latino youths; second, we point out the idiosyncrasies associated with AOD use among Latino youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 186 publications
(286 reference statements)
0
13
0
Order By: Relevance
“…Consistent with calls from other researchers, additional studies are needed to understand the particular socio-environmental factors that influence immigrant youths’ adoption of risk behaviors such as substance use upon arrival in the US (Kulis et al, 2007; Frank, 2010; Frank, 2007). Results of this study point to the continued importance of considering the effects of gender, the socio-cultural environment and the unique experience of the audience in designing effective preventive intervention programs for substance use among youth (Cox et al, 2011). …”
Section: Discussionmentioning
confidence: 94%
“…Consistent with calls from other researchers, additional studies are needed to understand the particular socio-environmental factors that influence immigrant youths’ adoption of risk behaviors such as substance use upon arrival in the US (Kulis et al, 2007; Frank, 2010; Frank, 2007). Results of this study point to the continued importance of considering the effects of gender, the socio-cultural environment and the unique experience of the audience in designing effective preventive intervention programs for substance use among youth (Cox et al, 2011). …”
Section: Discussionmentioning
confidence: 94%
“…Various mechanisms have been identified that might explain the manner in which greater acculturation is related to increased substance use [6, 7, 27]. Among these, discrimination has been identified as a construct that might function to explain part of the relationship between acculturation and substance use [12, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Although drinking is an individual behavior, forces, such as drinking norms, that exist across levels of social organization-from the family through peer groups, schools, regional and ethnic subcultures, and larger cultural contexts-may influence adolescent drinking (Cox et al, 2011). The question is how readily these drinking norms cross cultural boundaries.…”
Section: Cultural Hegemony and Social Learningmentioning
confidence: 97%
“…Both social learning and social contagion, as well as cultural norms that differ across ethnicities and many other factors, probably affect drinking levels (Cox et al, 2011;Wallace & Muroff, 2001). What the results mean, however, is that one cannot assume that the factors relevant to drinking behaviors, including but not limited to exposure to Whites, exhibit the same patterns across racial and ethnic groups.…”
Section: Social Learning Versus Peer Contagionmentioning
confidence: 99%